2016
DOI: 10.11646/zootaxa.4139.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new species of Sitana Cuvier, 1829 from southern India

Abstract: A new species of Sitana to the ponticeriana group is described herein from southern Tamil Nadu, India. Sitana marudhamneydhal sp.nov. is most similar to Sitana visiri, from which it differs in body scalation and dewlap size. Much like Sitana visiri, the breeding of this species coincides with the North-East monsoon rains (October to December), an adaptation related to its geographic location which receives higher rainfall during the North-East monsoon than the South-West monsoon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The microplastic which existed in fish's stomach it was a group of fragment, pellets, and lines ranging in size between 0.5 -4 mm, maybe exist pellets because the region near to industrial towns Tangier, Martil and a new port Tanger Med, and Sewage discharge to the sea water in M'diq Undoubtedly, much of the sea debris at the bottom of the sea will produce a lot of small marine debris as a result of decomposition and ingested microplastic by fish's. at new study 32 of fish specimens belonging 11 species and 9 families, Plastic pellets were found in the stomachs of 7 individuals (22%) of two species: the king mackerel, Scomberomorus cavalla (Scombridae), (Carcharhinidae) [28]. with sizes ranging from 2 to 5 mm in their longest dimension [26].…”
Section: Diplodus Cervinusmentioning
confidence: 93%
“…The microplastic which existed in fish's stomach it was a group of fragment, pellets, and lines ranging in size between 0.5 -4 mm, maybe exist pellets because the region near to industrial towns Tangier, Martil and a new port Tanger Med, and Sewage discharge to the sea water in M'diq Undoubtedly, much of the sea debris at the bottom of the sea will produce a lot of small marine debris as a result of decomposition and ingested microplastic by fish's. at new study 32 of fish specimens belonging 11 species and 9 families, Plastic pellets were found in the stomachs of 7 individuals (22%) of two species: the king mackerel, Scomberomorus cavalla (Scombridae), (Carcharhinidae) [28]. with sizes ranging from 2 to 5 mm in their longest dimension [26].…”
Section: Diplodus Cervinusmentioning
confidence: 93%